Recent use of habitat service value for tourism and impacts on coral reefs in the target destinations in Southern Vietnam - Ben, Hoang Xuan; Tuan, Vo Si (Vietnam Journal of Marine Science and Technology, 2019)
Coral reef-based tourism has developed quickly in Southern Vietnam, taking into account the target locations namely Cu Lao Cham islands, Nha Trang bay, Ninh Thuan and Phu Quoc islands during last decade. Among them, Nha Trang bay had longer history of marine tourism, starting with inshore development and expanding to islands in and around the bay. Tourist activities in Cu Lao Cham islands and Ninh Thuan were developed in linkages with MPA development and management. Meanwhile, Phu Quoc had become a new destination and drawn huge investments for extensive development of tourism in the islands. Economic value that was brought from use of coral reefs for tourism has increased significantly. For example, the payment of entry fee to Cu Lao Cham MPA has quickly increased year by year, reaching approximately 700,000 USD in 2018 and that in Ninh Thuan around 50,000 in 2017 and up to 200,000 USD in 2018. Reclamation for infrastructure building on inshore land and islands was considered as a serious impact, resulting in loss of terrestrial and underwater habitats (e.g. loss of Melaleuca forest in Phu Quoc islands or seagrass beds and coral reefs in Nha Trang bay) and increased sediment loading to coral reefs. Overexploitation of living resources for high food and souvenir demands occurred at all areas, leading to modification of communities, poorness and uncertainty for resource recruitment. Among these tree areas, Phu Quoc waters are the most vulnerable to coral bleaching due to increased surface temperature with records of mass bleaching in 2010 and 2016. Although MPAs existed in all study areas, role of conservationists in developing coral reef tourism was significantly considerable only in Cu Lao Cham case but poor in others. Local managers and businesses should pay more attention to sustainability in order to ensure not only coral reef conservation but also long-term benefits of local communities and tourist sector itself.